2017
DOI: 10.1094/mpmi-11-16-0240-r
|View full text |Cite
|
Sign up to set email alerts
|

Fall Armyworm-Associated Gut Bacteria Modulate Plant Defense Responses

Abstract: Mechanical damage caused by insect feeding along with components present in insect saliva and oral secretions are known to induce jasmonic acid-mediated defense responses in plants. This study investigated the effects of bacteria from oral secretions of the fall armyworm Spodoptera frugiperda on herbivore-induced defenses in tomato and maize plants. Using culture-dependent methods, we identified seven different bacterial isolates belonging to the family Enterobacteriacea from the oral secretions of field-colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 51 publications
7
103
0
Order By: Relevance
“…Only three samples, two adult males from Kitale (Kitale-m2 and Kitale-m3) and one larvae from Ngeria (Ngeria-l2) were dominated by Firmicutes. Four genera of bacteria, Pseudomonas, Delftia, Enterococcus and Serratia that were recorded in this study have 15 previously been isolated from S. frugiperda (De Almeida et al 2017; Acevedo et al 2017). Surprisingly, Staphylococcus, Microbacterium, Arthrobacter and Leclercia that were previously isolated from S. frugiperda in Brazil (De Almeida et al 2017) were not found in any of the samples we profiled in Kenya.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Only three samples, two adult males from Kitale (Kitale-m2 and Kitale-m3) and one larvae from Ngeria (Ngeria-l2) were dominated by Firmicutes. Four genera of bacteria, Pseudomonas, Delftia, Enterococcus and Serratia that were recorded in this study have 15 previously been isolated from S. frugiperda (De Almeida et al 2017; Acevedo et al 2017). Surprisingly, Staphylococcus, Microbacterium, Arthrobacter and Leclercia that were previously isolated from S. frugiperda in Brazil (De Almeida et al 2017) were not found in any of the samples we profiled in Kenya.…”
Section: Discussionmentioning
confidence: 82%
“…Symbiotic bacteria play a key role in the biology of insects. We characterized the gut bacterial communities in S. frugiperda larvae and adult samples collected from several locations in Kenya, finding some important differences and similarities across samples and in relation to other studies on this species (Acevedo et al 2017; De Almeida et al 2017). Understanding the gut microbial symbionts of this pest species may facilitate the development of novel, cost-effective control strategies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Leaf tissue (60–90 mg) frozen in liquid nitrogen was homogenized in a GenoGrinder 2000 (OPS Diagnostics, Lebanon, NJ, USA) and total RNA extracted using a modified Trizol protocol previously described (Acevedo et al ., ). Complementary DNA (cDNA) was synthesized from 1 μg of RNA using the High Capacity cDNA Reverse Transcription kit (Applied Biosystems) using Oligo‐dT following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 97%
“…It is well known that oral secretions from caterpillars induce defenses in plants; however, caterpillars do not always secrete regurgitant during feeding (Peiffer & Felton, ). Therefore, we first quantified the amount of regurgitant secreted by the FAW strains on their host plants following a previously described procedure (Peiffer & Felton, ; Acevedo et al ., ), and then tested the plant defense response to the application of those regurgitant quantities. Regurgitant was collected from the oral cavity of plant‐fed caterpillars (by gently tapping their heads) and immediately placed on ice.…”
Section: Methodsmentioning
confidence: 99%